Recuperarea de bunuri infracţionale pe plan internaţional: dimensiunea statistică [Articol] - Scorpan, Alesea (CEP USM, 2021)
The purpose of the article is to describe the evidence of the impact of international asset recovery and anti-money laundering efforts on poverty reduction and accountability of political elites using several evaluation methodologies, especially their consolidation for a better understanding of the proposed theme. The article shows the use of recovered assets on poverty reduction and gives evidence from successful cases, taking into account that the analyzed cases were several years ago and their impact now can be measured on the statistical scale.
ASSET RECOVERY ON THE INTERNATIONAL LEVEL: THE STATISTICAL DIMENSION
Keywords: asset recovery; poverty; corruption; criminality; confiscation; seizure